NEPEMIGRA/UFRGS: uma constelação de saberes e experiências para a formação da cidadania global a partir da pesquisa e da extensão em mobilidade humana - Rosa, Carolina Schenatto da (Universidade do Vale do Rio dos Sinos, 2022)
This research investigated pedagogical processes that emerge from the experiences and practices of the Núcleo de Estudos, Pesquisa e Extensão sobre Migrações da UFRGS (NEPEMIGRA) and their potential for the formation of citizenship in a global perspective. The choice of theme was due to the understanding that the dialogic relations between the research and extension practices developed by NEPEMIGRA can be configured as a training process strongly guided by student protagonism, participation and co-production of knowledge. The objective of this research was to analyze the experience of NEPEMIGRA from the relationship between teaching, research and extension for the formation of citizenship in a global perspective. The Grounded Theory, following the assumptions of Kathy Charmaz, was used as an approach for the construction of a study guided by the abductive logic, which combined interviews and document analysis to answer the following question: what are the contributions of NEPEMIGRA to the formation of citizenship in global perspective? Data analysis allowed us to understand the experiences and practices of the NEPEMIGRA from four dimensions: a) pedagogical dimension; b) political dimension; c) community dimension; d) dimension of procedural and interventional planning. From the relationship established between them, it was possible to conclude: NEPEMIGRA is constituted as an internationalization movement, as an exercise of dialogic interaction and intercultural practice; inter-institutional partnerships and the production of interdisciplinary knowledge are articulated to promote impact on student training and social transformation; the inseparability of teaching-research-extension is a pedagogical principle of intervention in the world and political incidence; epistemic equality is the methodological assumption for inter-knowledge and the pedagogical mediation built from these elements characterizes citizenship in a global perspective present in the process of collective formation promoted by NEPEMIGRA.

Este trabajo investigó procesos pedagógicos que emergen de las experiencias y prácticas del Núcleo de Estudos, Pesquisa e Extensão sobre Migrações da UFRGS (NEPEMIGRA) y sus potencialidades para la formación de la ciudadanía en perspectiva global. La elección del tema se debió a la comprensión de que las relaciones dialógicas entre las prácticas de investigación y extensión desarrolladas por el NEPEMIGRA pueden configurarse como un proceso de formación fuertemente pautado por el protagonismo estudiantil, la participación y la coproducción de conocimiento. El objetivo de esta investigación fue analizar la experiencia del NEPEMIGRA a partir de las relaciónes entre docencia, investigación y extensión para la formación de ciudadanía en una perspectiva global. La Teoría Fundamentada en los Datos, siguiendo los presupuestos de Kathy Charmaz, fue adoptada como abordaje para la construcción de un estudio guiado por la lógica abductiva, que combinó entrevistas y análisis documental para responder a la siguiente pregunta: ¿Cuáles son las contribuciones del NEPEMIGRA para la formación de la ciudadanía en perspectiva global? El análisis de datos permitió comprender las experiencias y prácticas del Núcleo desde cuatro dimensiones: a) dimensión pedagógica; b) dimensión política; c) dimensión comunitaria; d) dimensión de planificación procesal e interventiva. De la relación establecida entre ellas, fue posible concluir que el Núcleo se constituye como un movimiento de internacionalización, como un ejercicio de interacción dialógica y práctica intercultural; que las colaboraciones interinstitucionales y la producción de conocimiento interdisciplinar se articulan para promover el impacto en la formación de los estudiantes y el impacto y la transformación social; que la inseparabilidad entre docencia-investigación-extensión es un principio pedagógico de intervención en el mundo e incidencia política; que la igualdad epistémica es el presupuesto metodológico para el interconocimiento y que la mediación pedagógica construida a partir de estos elementos es lo que caracteriza la ciudadanía en perspectiva global presente en el proceso de formación colectiva promovido por el Núcleo.
Keywords: Cidadania global; Migrações; Universidade; Pesquisa; Extensão; Global citizenship; Migrations; University; Research; University extension; Ciudadanía global; Migraciones; Universidad; Investigación; Extensión; ACCNPQ::Ciências Humanas::Educação